AKTIVITAS EKSTRAK ETANOL DAUN SIRIH MERAH (Piper ornatum) SEBAGAI INSECT GROWTH REGULATOR TERHADAP LARVA Aedes aegypti - Prasidina, Alive Ginang; Joharman, Joharman; Wydiamala, Erida (Universitas Lambung Mangkurat, 2024)
Abstract: Dengue Hemorrhagic Fever is a disease transmitted through Aedes aegypti mosquitoes, which can be prevented using larvicides. Prolonged use of larvicides leads to mosquito resistance. As an alternative, Insect Growth Regulators (IGRs) are employed. Red betel leaves (Piper ornatum) can be utilized as an IGR. Piper ornatum contains secondary metabolites (flavonoids, alkaloids, tannins) that have the potential as IGRs. This research aims to analyze the activity of an ethanol extract of Piper ornatum leaves as an IGR against Aedes aegypti larvae. The study employed the true experimental method with a post-test only control group design consisting of 6 treatment groups: 0.3%, 0.4%, 0.5%, 1.5%, negative control (aquadest), and positive control (pyriproxyfen 0.025mg/L). Treatments were applied to third instar larvae for 7 days with 4 repetitions. The observations were calculated using the Inhibition Emergence (IE) Adult% formula. The results indicated that all concentrations of the ethanol extract of Piper ornatum leaves exhibited IGR activity against Aedes aegypti, with an IE Adult% of 100% in the concentration range of 0.3%, 0.4%, 0.5%, and 1.5%. Keywords: Aedes aegypti, Insect Growth Regulator, Red Betel Abstrak: Demam Berdarah Dengue merupakan penyakit yang ditularkan melalui Aedes aegypti, yang dapat dicegah menggunakan larvasida. Penggunaan larvasida dalam waktu lama menyebabkan resistensi nyamuk tersebut. Sebagai alternatif, digunakan Insect Growth Regulator (IGR). Daun sirih merah (Piper ornatum) bisa dimanfaatkan menjadi IGR. Piper ornatum mengandung senyawa metabolit sekunder (flavonoid, alkaloid, tanin) yang berpotensi sebagai IGR. Penelitian ini bertujuan untuk menganalisis aktivitas IGR ekstrak etanol daun Piper ornatum terhadap larva Aedes aegypti. Penelitian ini menggunakan metode true experimental dengan rancangan post test only with control group design dari 6 kelompok perlakuan: 0,3%, 0,4%, 0,5%, 1,5%, kontrol negatif (aquadest), dan kontrol positif (pyriproxyfen 0,025mg/L). Perlakuan dipaparkan terhadap larva instar III selama 7 hari dengan 4 kali pengulangan. Hasil pengamatan dihitung menggunakan rumus Inhibition Emergence (IE) Adult%. Hasil menunjukkan semua konsentrasi ekstrak etanol daun Piper ornatum memiliki aktivitas IGR terhadap Aedes aegypti dengan IE Adult% sebesar 100% pada rentang konsentrasi 0.3%, 0.4%, 0.5%, dan 1.5%. Kata-kata kunci: Aedes aegypti, Insect Growth Regulator, sirih merah